Hubungan Panjang Tungkai Bawah dengan Kelincahan Atlet Pencak Silat di Padepokan Untung Surapati Kartasura - Subagiyo S, Ilham, Wahyuni SST.,FT.,M.Kes (2017)
ABSTRACT DEPARTEMENT OF PHYSIOTHERAPY FACULTY OF HEALTH SCIENCE UNIVERSITY MUHAMMADIYAH OF SURAKARTA SKRIPSI, 28 APRIL 2017 ILHAM SUBAGIYO S / J120130036 "THE CORRELATION OF LENGTH OF LOWER LEG WITH ATHLETE'S AGILITY OF PENCAK SILAT IN PADEPOKAN PENCAK SILAT UNTUNG SURAPATI KARTASURA" (Guided by: Wahyuni, SSt.FT., M.Kes) Background : Pencak silat is one kind of sport especially in indonesia. Althought the athlete of pencak silat had joined the exercise program from the coach, in fase the athlet achievement in international event are up and down. That is caused by physical factor which less of attention one of them is length of leg. There is possibilities that the length of leg influence the agility in fighting. So it also influence to the athlete achievement. Objective : For knowing the correlation between the length of lower leg to athlete agility of pencak silat in Padepokan Untung Surapati Kartasura. The Benefit : Being able to know the correlation between the length of lower leg to athlete agility of pencak silat in Padepokan Pencak Silat Untung Surapati Kartasura. Method : The method which used in this research was observational with cross sectional approach. The sample taking technique by purposive sampling with total of sample are 92 people. To measure the length of lower leg is using meter line from trochantor to the floor while to measure the agility is running as fast as possible pass throught the cone which in the way was made. The correlation test using pearson test with degree of confident as 95 %. Result : Based on pearson test known that P-Value 0,000<0,005 so Ho was rejected and Ho is accepted. So it can be interpreted that there was correlation betwen the length of lower leg with athlete agility of pencak silat in Padepokan Pencak Silat Untung Surapati Kartasura. Conclusion : There was correlation between the length of lower leg with athlete agility of pencak silat in Padepokan Pencak Silat Untung Surapati Kartasura. Keywords : Length limb, Agility, Pencak Silat